The Drama of German Expressionism A German-English Bibliography - Hill, Claude (UNC Studies in the Germanic Languages and Literatures, 1960)
Originally published in 1960, this bibliography with more than five thousand items provided an indispensable tool for those interested in the German expressionist plays. The volume contains a general bibliography on German expressionistic drama and as well as sixteen leading German playwrights: Barlach, Brecht, Bronnen, Goering, Hasenclever, Jahnn, Johst, Kaiser, Kokoschka, Kornfeld, Rubiner, Sorge, Sternheim, Toller, Unruh, and Werfel.